1982
DOI: 10.1002/cber.19821150127
|View full text |Cite
|
Sign up to set email alerts
|

Elektrochemische Oxidation, VII. Synthese und Struktur von 7‐tert‐Butyl‐2‐methylbenzoxazolen

Abstract: Die anodische Oxidation von 15 tert‐butyl‐substituierten Phenolen 1a–o in wasserfreiem Acetonitril oder in Acetonitril/Perchlorsäure führt zu den entsprechenden 7‐tert‐Butyl‐2‐methylbenzoxazolen 3a–o. Der Strukturbeweis wurde durch unabhängige Synthese von 3k und 13C‐NMR‐Spektroskopie sowie durch Röntgenstrukturanalyse von 7‐tert‐Butyl‐2‐methyl‐5‐benzoxazolcarbaldehyd (3i) geführt. Der Einfluß des Elektrolytsystems auf die Produktbildung wird diskutiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Actually, it differs by about 13 ppm. The signals for the 3-methyl groups in both compounds appear roughly at 11 ppm, which is also typical for fused 3-methyl-isoxazoles [17±22] and not for 2-methyl-oxazoles resonating usually at 14 ppm [16,23,24]. Moreover, an oxazolopyridinone structure is de®nitely ruled out by comparison with the corresponding shifts for the above-mentioned reference compounds in the 13 C NMR spectra, suggesting good correlations only between 8, 9 and 3-methyl-isoxazoloquinolones.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Actually, it differs by about 13 ppm. The signals for the 3-methyl groups in both compounds appear roughly at 11 ppm, which is also typical for fused 3-methyl-isoxazoles [17±22] and not for 2-methyl-oxazoles resonating usually at 14 ppm [16,23,24]. Moreover, an oxazolopyridinone structure is de®nitely ruled out by comparison with the corresponding shifts for the above-mentioned reference compounds in the 13 C NMR spectra, suggesting good correlations only between 8, 9 and 3-methyl-isoxazoloquinolones.…”
Section: Resultsmentioning
confidence: 97%
“…Some authors revealed confusion of previously published fused isoxazoles with the corresponding oxazoles or reported about remaining uncertainties concerning that isomer problem when structure elucidation was based solely on spectroscopic methods [8,16]. Evidence of structure was furnished by alternative syntheses, respectively [8,16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The accessible potential range depends upon the solvent and the supporting electrolyte that are used. Typical cyclic voltammogram (anodic oxidation followed by cathodic reduction) was performed [18][19][20][21].…”
Section: Electrochemistrymentioning
confidence: 99%
“…For reference structural data, see: Bruno et al (2004). For related benzoxazole structures, see: Dreher et al (1982); Mrozek et al (1999); Qu et al (2008).…”
Section: Related Literaturementioning
confidence: 99%